(untitled) (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
HIV infection, Syphilis and Hepatitis B are disease contagious that arrived moment This Still become problem health in the world including Mataram City, West Nusa Tenggara. HIV transmission from Mother to child by 20-45%, transmission Syphilis from Mother to child by 69-80% and transmission of Hepatitis B to the mother pregnant to child by 90-95%. Control transmission of HIV/AIDS from partner endeavored through inspection Triple Elimination in the candidate’s bride, as completeness condition married. Objective in This study aims to explore the anxiety of candidate’s bride and groom in the Triple Elimination Test for HIV, Syphilis and Hepatitis B at the Health Center Pumpkin. Method: Research This use approach quantitative characteristic descriptive analytic with cross -sectional design. Data analysis includes bivariate analysis for expose distribution frequency each variable. Questionnaire worry use HARS scale. Result: Obtained results through statistical test analysis knowledge with worry using an alternative test Kolmogrov Smirnov with value ρ value = 0.004 if compared to with α = 0.05 then ρ value < 0.05. Attitude Results with worry using an alternative test Kolmogrov Smirnov with value ρ value = 0.037 if compared to with α = 0.05 then ρ value < 0.05. Conclusion: Conclusion in study This is exists candidate anxiety _ coming bride _ to public health center Pumpkin For check Triple Elimination, so There is connection knowledge and attitude with anxiety in HIV/AIDS patients. From the results study This suggested for researcher next to research other variables that have not researched like support deep psychological and social Triple Elimination check